PENGARUH PENGALAMAN KERJA DAN PENGEMBANGAN KARIR TERHADAP KINERJA KARYAWAN PADA PT SINAR NIAGA SEJAHTERA KOTA LUBUKLINGGAU - Suwarno Suwarno; Ronal Aprianto (Universitas Gunadarma, 2019)
This research was conducted at PT Sinar Niaga Sejahtera with the formulation of the problem in this study is whether work experience affects employee performance, whether career development affects employee performance, and whether work experience and career development affect employee performance. The research method used is a quantitative method with a sample of 32 people who are employees of PT Sinar Niaga Sejahtera and the data collection technique used is questionnaires. Data analysis techniques used are multiple regression analysis. The result of the regression that works experience influenced employee performance and career development influenced employee performance.